Artificial Barrier As To Enhance Removal Of E.Coli In Riverbank Filtration - Rashid, Nur Aziemah Abd (2019)
Riverbank filtration (RBF) is a water abstraction method which has a multi-barrier to remove many pollutants. However, some RBF sites report that the multi-barrier may be not effective in certain circumstances. This study has made such related verification and from the monitoring result of 18 months data (2015-2017) at Lubok Buntar, sites in Kedah, showed that pollutants and E. coli that were not present in the wells of the tubes appeared on rainy days, and the initial concentration of E. coli was mostly absent in normal days. In order to mitigate and pre-treat the water abstraction intake so that the removal of E. coli can be sustained in a long term operation, this study suggested an artificial barrier for application at RBF sites. An artificial barrier is a vertical barrier which contain layer of granular activated carbon (GAC) and zeolite near the tube well. The preliminary results of GAC and zeolite to adsorb E. coli shows that both media suitable where it removed 100% of E. coli in acidic environment. This study focuses on a laboratory scale artificial barrier using a column test and The Mixture methodology concerning simplex lattice was used to optimize the media proportion in removing E. coli. Initially, soil (Soil A, B and C) gave the highest of E. coli removal with 100% eliminations. However, over time, the removal of E. coli has decreased significantly and the application of artificial barrier with soil provides a more consistent removal compared using solitary soil only selection. The optimum ratio for local soil A is 60% local soil, 16% GAC and 24 % zeolite. Local soil B is local soil 74% and zeolite 26%. Local soil C is local soil 62%, GAC 14% and zeolite 24%. The breakthrough analysis shows that the adsorption model for E. coli follow Thomas and not Yoon-Nelson model. The optimum data acquire from the mixture methodology also proved that this proportion is suitable to be applied under anaerobic condition at different flowrates. Finally, this research demonstrates the capability of artificial barrier to enhance the alluvial soil characteristics to eliminate contaminants which are effective for RBF application as mitigation measure. These findings support the need of subsequent purification processes, the so-called second protective barrier.